Prestarlike functions with negative coefficients - H. Silverman; E. M. Silvia (International Journal of Mathematics and Mathematical Sciences)
The extreme points for prestarlike functions having negative coefficients are determined. Coefficient, distortion and radii of univalence, starlikeness, and convexity theorems are also obtained.